PRELIMINARY FIELD OBSERVATIONS ON NEOTROPICAL ECHINOCOCCOSIS IN SURINAME - Oostburg, Baltus E J.; Eersel, Marthelise; Vrede, Martinus A.; Gottstein, Bruno; Rausch, Robert L.; D’Alessandro, Antonio (Revista de Patologia Tropical / Journal of Tropical Pathology, 2008)
The objective of this preliminary field investigation was to examine circumstances by which residents of Suriname might be exposed to metacestode infections of neotropical Echinococcus species. We visited the areas where the 8 humaris cases of polycystic echinococcosis probably had acquired the infection (7 cases infected by E. vogeli and one by E. oligarthrus). This note summarizes the observations obtained during a twoweek visit. The wiid dog Speothus venaticus (cachorro-do-mato in Brazil: bush dog in English) was known mainly by name, only few persons had ever seen one. It is also known for its hunting preference for pacas. Pacas are abundant and esteemed for the quality of their meat. These animais are the only 2 natural hosts of Echinococcus vogeli in nature. Despite the few animais and persons studied, the positive results of the observations fuifilled the objective of the visit: the location of friendly rural human populations in arcas where cases of polycystic echinococcOsis had been diagnosed, where pacas were abundant and frequentiy hunted, and where domestic dogs were numerous. The viliages of Witagron and Kaaimanston were selected as the best for a future study. In addition of having the characteristics mentioned above they were located within 2 hours by car from the capital. Furthermore, they are visited monthly by medical personnel, including a physician from the Medical Mission. The custom of feeding the viscera of